Gametocytes from K13 propeller mutant plasmodium falciparum clinical isolates demonstrate reduced susceptibility to dihydroartemisinin in the male gamete exflagellation inhibition assay - Lozano, S; Gamallo, P; González-Cortés, C; Matilla, J-L; Fairhurst, RM; Herreros, E; Amaratunga, C; Rodrigues, J (American Society for Microbiology, 2018)
Mutations in the kelch propeller domain (K13 propeller) of Plasmodium falciparum parasites from Southeast Asia are associated with reduced susceptibility to artemisinin. We exposed in vitro-cultured stage V gametocytes from Cambodian K13 propeller mutant parasites to dihydroartemisinin and evaluated the inhibition of male gamete formation in an in vitro exflagellation inhibition assay (EIA). Gametocytes with the R539T and C580Y K13 propeller alleles were less susceptible to dihydroartemisinin and had significantly higher 50% inhibitory concentrations (IC50s) than did gametocytes with wild-type alleles.